The Effect of Passing Accuracy in Football Training Using the Inside and Back Foot of Male Football Players, Rajabhat Maha Sarakham University - Srimuang, Tanawanaphorn; Amartmontr, Wissanu; Kethom, Krit (Journal of Education Rajabhat Maha Sarakham University, 2022)
The purpose of this research was to study the effect of passing accuracy in football training using the inside and back foot of male football players, Rajabhat Maha Sarakham University. The sample of the study consisted of 20 football players selected participants in purposive sampling. The population was divided into 2 groups of 10 people each. The members of group 1 practice passing the ball accurately with both the inside and the back foot, where as the members of group 2 performed with a regular program, working out 3 days a week, and 4 weeks in a month. The data were analyzed by mean, standard deviation, t-test dependent, and the t-test independent. The statistical significance level was at .05. The research results showed that the effect of passing accuracy in football training using both the inside and the back foot between the 2 groups, performed before and after training, was statistically significant difference at the .05 level. According to the results, using the inside and back foot to pass the ball can affect the team’s performance on developing and increasing the accuracy during practicing.